Relationships Weight Loss Mother With Hormonal Birth Control Usage - Rika Herawati; Romy Wahyuny (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
Family planning, according to WHO (world health organization) expert commite 1970 is action that helps couples to avoid unwanted pregnancies, getting birth highly desired, set the interval between pregnancies and determine the number of children in the family (Sulistyawati, 2018). Objective To determine the relationship research Mom Weight Loss with use of hormonal birth control in the village Pekan Tebih Puskesmas Rokan Hulu. The research method used is Analytical Survey and the type of cross-sectional study. The population in the study were all women taking hormonal birth control as many as 129 people and the sample is saturated sample as many as 129 people. Results of research on the relationship of maternal weight with the use of hormonal birth control only get 69 respondents who are willing to be investigated, while the rest are not willing to study for a variety of reasons given by the respondents. Based on the data obtained is processed using computerized women taking birth control pills that there were 18 respondents (23.1%) and taking injections were 51 people (73.9%). Conclusion There is a relationship Weight Mom With Hormonal birth Pemakian Pekan Tebih Village Puskesmas Kepenuhan Hulu. Expected advice for other researchers can continue research on the use of mother Weight Loss Hormonal birth control and be used as a reference / reading especially things related about hormonal birth control. Keywords: Hormonal Birth Control, Birth Control, Weight Loss